Realistic Mathematics Education Approach Based on Ethnomathematics of the Sunan Bonang Gate in Elementary School - Windha Ana Sevia (ARITMATIKA: Jurnal Riset Pendidikan Matematika, 2025)
Mathematics needs to be taught using the right approach because many students think it is a difficult subject. This difficulty often happens because the lessons are too abstract and not connected to students’ real-life experiences. This study aims to apply mathematics learning using the Realistic Mathematics Education (RME) approach based on ethnomathematics, supported by a Hypothetical Learning Trajectory (HLT), in the topic of recognizing two-dimensional shapes for second-grade students at SDN Karangrejo I. The local cultural context used is the ornament of the Sunan Bonang Gate in Tuban, which includes geometric shapes and is familiar to the students' daily lives. This research used a design-based research method with three stages: preparatory design, design experiment, and retrospective analysis. Data were collected through observation, interviews, documentation, and student worksheets. The results showed that the learning process followed the steps in the HLT and helped improve students’ understanding of two-dimensional shapes. Students became more active, could name the shapes correctly, and give examples from their surroundings.